Taking control: Power and contradiction in First Nations Adult Education - Haig-Brown, Celia (UBC PR, 1995)
This book is a critical ethnography of the Native Education Centre (NEC) in Vancouver, British Columbia. It presents an intimate view of the center, focusing on the people that work there--First Nations students, board members, teachers--and revealing their beliefs about First Nations control of education and how they put those beliefs into practice. Fieldwork was conducted at NEC during the 1988-89 school year, at which time over 400 adult students were enrolled in 11 programs ranging from basic literacy to "skills training." The chapters of the book are structured to lead through the various processes of research involvement, thereby replicating the temporal and spatial bases of development of the researcher's understandings. Following a tour of the NEC building and its surroundings, Part 1 provides a framework of concepts related to power, culture, and control, drawing particularly on Foucault; describes the conduct of the research, including how the non-Native researcher began and proceeded in her relationship with NEC participants; highlights episodes in the struggle for First Nations control of education; and outlines the history of NEC. Part 2 uses interview excerpts to convey the feelings of students and staff about NEC as a place and about the programs offered there, as well as their explicit thoughts about Indian control of Indian education, power relations, and Native values. Part 3 sums up major themes of the study, focusing on the contradictions inherent in an institution that prepares Indian students to participate in an exclusionary non-Native society while attempting to enhance their appreciation of their own cultures and heritages. Contains over 200 references, an index, and interview questions. (SV)